Red Planet stage 7 - Hunt, Rodrick (United Kingdom Oxford University Press, 2012)
In this space-themed adventure, Biff, Chip, Wilf, and even Floppy blast off on an interplanetary journey. They travel to the Red Planet, meet space creatures, and explore an exciting cosmic setting$1 (Bthough Floppy is less enthusiastic than his friends!s
These books are part of the Oxford Reading Tree Level 7: Stories series, designed for children who are developing confidence and fluency in reading. The stories continue the popular adventures of Biff, Chip, Kipper, Wilf, and friends, combining everyday school life with imaginative journeys sparked by the magic key.